Modelagem Cross-Layer da qualidade de experiência para transmissões de vídeo em sistemas sem fio OFDM - CASTRO, Bruno Souza Lyra (Universidade Federal do Pará, 2014)
This work presents a study about video transmission in wireless systems. The applied methodology aims to prove the existence of a direct relationship between BER and quality loss (PSNR loss) on video streams in OFDM (Orthogonal Frequency Division) systems. The results were obtained from simulations, developed in MatlabTM environment, and, measurements in real scenarios, held on university campus and inside the research laboratory in an controlled environment. From the comparison between simulated and measured data it was possible to prove the relationship between BER and PSNR loss, which led to the formulation of an empirical Cross-Layer Model with exponential characteristic. The modeling has obtained a RMS error and standard deviation close to 1.65 dB when compared to simulations. Moreover, its validation was performed from data obtained from real-world scenarios, which were not used to adjust the parameters of the proposed equation. This Cross-Layer model does not depend on the type of channel or coding in FEC (Forward Error Correction), allowing future integration with commercial or open-source network planning softwares.